2021
DOI: 10.3390/antibiotics10050491
|View full text |Cite
|
Sign up to set email alerts
|

New Sequence Type ST3449 in Multidrug-Resistant Pseudomonas aeruginosa Isolates from a Cystic Fibrosis Patient

Abstract: Pseudomonas aeruginosa is one of the most critical bacterial pathogens associated with chronic infections in cystic fibrosis patients. Here we show the phenotypic and genotypic characterization of five consecutive multidrug-resistant isolates of P. aeruginosa collected during a month from a CF patient with end-stage lung disease and fatal outcome. The isolates exhibited distinct colony morphologies and pigmentation and differences in their capacity to produce biofilm and virulence potential evaluated in larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…Regarding AmpC polymorphisms, the T105A substitution was detected in most of the isolates, which has been correlated with more efficient carbapenem and cefepime hydrolysis (Cabot et al, 2012). Furthermore, some mutations detected in PmrA and PmrB were observed previously in colistin-sensitive strains (Snesrud et al, 2018); also, some of the alterations in OprD had been described before with no contribution to carbapenem resistance (Horna et al, 2018;Díaz-Ríos et al, 2021).…”
Section: Diverse Genetic Background Of Multidrug-resistant Pseudomonas Aeruginosa Isolates Carrying Bla Kpc /Bla Vimmentioning
confidence: 62%
“…Regarding AmpC polymorphisms, the T105A substitution was detected in most of the isolates, which has been correlated with more efficient carbapenem and cefepime hydrolysis (Cabot et al, 2012). Furthermore, some mutations detected in PmrA and PmrB were observed previously in colistin-sensitive strains (Snesrud et al, 2018); also, some of the alterations in OprD had been described before with no contribution to carbapenem resistance (Horna et al, 2018;Díaz-Ríos et al, 2021).…”
Section: Diverse Genetic Background Of Multidrug-resistant Pseudomonas Aeruginosa Isolates Carrying Bla Kpc /Bla Vimmentioning
confidence: 62%
“…Non-synonymous mutations have been reported also in the transcriptional regulator of MexAB-OprM, nalC [186]. The same clinical isolates have mutations which lead to the activation of MexT, the positive regulator of MexEF-OprN [186]. A high mutation rate was identified also in the genes encoding the components of RND efflux pumps, such as mexA, mexY, oprM [187] and mexB [188].…”
Section: Discussionmentioning
confidence: 99%
“…However, another work revealed mutations also in the efflux regulator genes mexR, mexT, and nfxB [185]. Non-synonymous mutations have been reported also in the transcriptional regulator of MexAB-OprM, nalC [186]. The same clinical isolates have mutations which lead to the activation of MexT, the positive regulator of MexEF-OprN [186].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with a previous report (Díaz-Ríos et al, 2021), a total of 220 virulence genes were found among their Pseudomonas biofilm-forming isolates by comparing their WGS and VFDB data. All the isolates were able to produce biofilm.…”
Section: ))mentioning
confidence: 92%